2016
DOI: 10.1126/sciadv.1600502
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-bound nanovesicles within ECM bioscaffolds

Abstract: Matrix-bound vesicles within ECM bioscaffolds provide mechanistic insight into inductive properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
283
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 286 publications
(298 citation statements)
references
References 69 publications
8
283
0
Order By: Relevance
“…A variety of growth factors are also retained within the ECM preparation, including transforming growth factor-β, vascular endothelial growth factor-A, basic fibroblast growth factor, and nerve growth factor [21], which all are known to influence neuronal and endothelial cells. In addition, matrix-bound nanovesicles (MBV) enriched in miRNA and other signaling molecules are present within the ECM preparation [33]. …”
Section: Methodsmentioning
confidence: 99%
“…A variety of growth factors are also retained within the ECM preparation, including transforming growth factor-β, vascular endothelial growth factor-A, basic fibroblast growth factor, and nerve growth factor [21], which all are known to influence neuronal and endothelial cells. In addition, matrix-bound nanovesicles (MBV) enriched in miRNA and other signaling molecules are present within the ECM preparation [33]. …”
Section: Methodsmentioning
confidence: 99%
“…A cryptic peptide derived from collagen IIIa showed chemotactic activity for many cells, including cortical neural stem cell and myoblasts in vitro and for cells showing stem-cell markers in vivo (Agrawal et al 2011b). Induction of both proliferation and differentiation of neural stem cells by UBM-ECM has been shown (Wang et al 2013a), and neural cell differentiation was later reproduced in neuroblastoma cells with MBVs isolated from UBM-ECM (Huleihel et al 2016). Primitive precursor cells seeded in decellularized kidney proliferated and expressed markers for site-appropriate differentiation (Ross et al 2009).…”
Section: Stem/progenitor Cell Recruitmentmentioning
confidence: 99%
“…MBVs are extracellular vesicles from 10 nm to 600 nm in size embedded within the ECM. MBVs are highly stable bodies that protect their microRNA (miRNA) cargo from degradation and are resistant to the enzymes and detergents used in tissue decellularization protocols (Huleihel et al 2016). miRNAs are small noncoding single-stranded RNA molecules of around 22 nucleotides in length that affect multiple biological processes through posttranscriptional gene regulation (Ling et al 2013 (Huleihel et al 2016).…”
Section: Production Of Ecm Bioscaffolds Extracellular Matrix Compositmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, EVs catalyse the crosslinking of collagen in the ECM via lysyl oxidase-like 2 (LOXL2), which is located on the exterior of the exosome membrane [126]. In addition, a study by Huleihel et al (2016) observed that EVs present within the ECM were closely associated with the collagen network of the matrix, but these EVs could be separated from the fibre network [127]. This may indicate that EVs attend to the ECM formation and function.…”
Section: Collagen Production and Ecm Remodellingmentioning
confidence: 99%